2009
DOI: 10.1136/bjsm.2009.058123
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of neuroimaging, balance testing, electrophysiology and blood markers to the assessment of sport-related concussion

Abstract: The current status of the diagnostic tests and investigations is analysed, and potential directions for future research are provided. Currently, all tests and investigations, with the exception of clinical balance testing, remain experimental. There is accumulating research, however, that shows promise for the future clinical application of functional magnetic resonance imaging in sport concussion assessment and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 112 publications
1
47
0
3
Order By: Relevance
“…However, the few studies conducted on younger athletes have not demonstrated significant differences in head injury characteristics or outcomes of athletes who possess these genetic markers. [127][128][129] At this time, genetic testing is not recommended for evaluating young athletes with concussion.…”
Section: Genetic Testingmentioning
confidence: 99%
“…However, the few studies conducted on younger athletes have not demonstrated significant differences in head injury characteristics or outcomes of athletes who possess these genetic markers. [127][128][129] At this time, genetic testing is not recommended for evaluating young athletes with concussion.…”
Section: Genetic Testingmentioning
confidence: 99%
“…27,28 Electrophysiological measures (i.e., electroencephalography [EEG] and event-related potential [ERP]) have revealed functional effects of concussion as much as 3 years post-injury, 29 even in the absence of behavioral effects. 30 In addition, a number of recent studies have used functional magnetic resonance imaging (fMRI) to examine functional abnormalities in recently concussed athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated more objective measures for concussion diagnosis, including balance testing, 20 neuropsychological testing, 21 and advanced imaging. 22 Whereas these measures assess the clinical symptoms of concussion, no measure can identify the concussed athlete while on the field or be used as a preventive tool. Head-impact biomechanics have been investigated to determine the kinematic signature of a concussion.…”
mentioning
confidence: 99%